Influence of Plant Population and Nitrogen-Fertilizer at Various Levels on Growth and Growth Efficiency of Maize. (15th September 2013) - Tajul, M. I.; Alam, M. M.; Hossain, S. M. M.; Naher, K.; Rafii, M. Y.; Latif, M. A.
Abstract : Field experiments were conducted to evaluate plant population and N-fertilizer effects on yield and yield components of maize ( Zea mays L.). Three levels of plant populations (53000, 66000, and 800000 plants ha −1 corresponding to spacings of 75 × 25, 60 × 25, and 50 × 25 cm) and 4 doses of N (100, 140, 180, and 220 kg ha −1 ) were the treatment variables. Results revealed that plant growth, light interception (LI), yield attributes, and grain yield varied significantly due to the variations in population density and N-rates. Crop growth rate (CGR) was the highest with the population of 80, 000 ha −1 receiving 220 kg N ha −1, while relative growth rate (RGR) showed an opposite trend of CGR. Light absorption was maximum when most of densely populated plant received the highest amount of N (220 kg N ha −1 ). Response of soil-plant-analysis development (SPAD) value as well as N-content to N-rates was found significant. Plant height was the maximum at the lowest plant density with the highest amount of N. Plants that received 180 kg N ha −1 with 80, 000 plants ha −1 had larger foliage, greater SPAD value, and higher amount of grains cob −1 that contributed to the maximum yield (5.03 t ha −1 ) and the maximum harvest index (HI) compared to the plants in other treatments.